Hetrogenous impact of interest rates on retail firm prices : a product-level analysis using micro-data from Lesotho - Mzezewa, Lerato (School of Economics, 2016)
Price-setting behaviour plays an important role in the transmission mechanism of monetary policy as pricing decisions of firms in the private sector determine how changes in the official rate affect prices. Several recent studies using micro price data have highlighted the importance of the variation in firm characteristics on pricing decisions. This study investigates whether firms adjust their prices in response to higher interest rates and whether this response differs for firms that have credit. We estimate multinomial logistic regression models using highly disaggregated panel data on monthly product prices of 131 retail outlets in Lesotho over the period 2002-2009. In general, our results suggest that firms are more likely to adjust their prices in response to an interest rate shock. Firms will either revise their prices upwards or downwards compared to keeping their prices constant. This ambiguity occurs when a firm's price is a function of price elasticity of demand and costs. A firm has to balance the need to pass on increased cost of the higher interest cost onto prices against the demand-side sensitivity to price increases. On the contrary, when comparing firms with credit to those without, our findings show that firms with credit are more likely to keep their prices constant than to revise them. Furthermore, the study finds asymmetric results in the direction of the price adjustments. Prices are more likely to increase or decrease in the presence of both a demand and a cost shock, whereas prices are more likely to remain constant in the presence of a cost shock only. No evidence was found that credit owing firms pass the higher cost of credit onto their prices, suggesting that firms with credit finance have access to cheaper financing options than firms without credit.